Positive stereotypes, negative outcomes: Reminders of the positive components of complementary gender stereotypes impair performance in counter‐stereotypical tasks - Kahalon, Rotem; Shnabel, Nurit; Becker, Julia C. (British journal of social psychology, 2018)
Gender stereotypes are complementary: Women are perceived to be communal but not agentic, whereas men are perceived to be agentic but not communal. The present research tested whether exposure to reminders of the positive components of these gender stereotypes can lead to stereotype threat and subsequent performance deficits on the complementary dimension. Study 1 (N = 116 female participants) revealed that compared to a control/no‐stereotype condition, exposure to reminders of the stereotype about women's communality (but not to reminders of the stereotype about women's beauty) impaired women's math performance. In Study 2 (N = 86 male participants), reminders of the stereotype about men's agency (vs. a control/no‐stereotype condition) impaired men's performance in a test of socio‐emotional abilities. Consistent with previous research on stereotype threat, in both studies the effect was evident among participants with high domain identification. These findings extend our understanding of the potentially adverse implications of seemingly positive gender stereotypes.